Interconnections of Asian diaspora : mapping the linkages and discontinuities - George, Sam (Christian writer) (Asian diaspora Christianity series ;, 2022)
"Asians make up the largest and most dispersed peoples of the world, and Christians make up a sizable proportion of this demographic. Asian Christians are more likely to emigrate, and many have continued to embrace Christian faith at their diasporic places of settlement. They are quick to establish distinctively Asian churches all over the world and infuse diversity, revival, and missionary consciousness into their adopted communities. They preserve the ties and cultures of their ancestral homelands while assimilating and adapting into the new setting. They have become a recognizable force in the transformation and advancement of Christianity itself at the beginning of the twenty-first century. The dozen essays in this volume are written by leading scholars of Asian backgrounds situated in various diasporic locations. The authors trace the contours of their dispersion and highlight diverse missiological themes, including the scattering (diaspora) and the gathering (ekklesia) of Asian Christians around the world. This volume traces the origins and destinations of major Asian migration and diaspora communities from a variety of perspectives and geographical locations. It is pan-Asian in scope and multidisciplinary in nature. It also provides the latest data and infographics on Asian diasporas worldwide." --